(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The healthcare system of Saudi Arabia needs to be modernized to achieve the targets of Vision 2030 and to meet future challenges of ensuring efficient, effective, and high-quality healthcare for all people in an affordable and accessible manner. The challenges in this respect are many. This review identified the challenges discussed in the literature. In the context of the rising demand for quality care due to the increasing population, especially of the elderly, increasing prevalence of chronic diseases, and pandemics, there is immense pressure on the capacities, workforce, and financial resources. Capacity enhancement by increasing the number of hospitals and beds will also lead to demand for an increased workforce. It has been pointed out that the current workforce strength and those likely to be added to it from the local population are inadequate even to achieve the Vision 2030 target. Technological solutions like telemedicine, e-health, and the Internet of Things may partially solve the problem. Financial resources will be a limiting factor to provide free healthcare for all Saudi citizens and the Saudi healthcare system will soon become unsustainable. Technology can ease out part of it. Additionally, privatization and private participation have been suggested in some papers, but objected to in a few other papers, as they see some negative aspects of privatization affecting the Saudi healthcare model. The solutions offered in the reviewed papers need to be tested before implementing them. More research to explore other solutions may also be beneficial.